Preparation-method-dependent morphological, band structural, microstructural, and photocatalytic properties of noble metal-GaNbO4 nanocomposites - Devi, Suman; Kelkar, Sarika A.; Kashid, Vikas; Salunke, Hemant G.; Gupta, Narendra M. (RSC Advances, 2013)
We report the distinct physicochemical and photophysical properties of gallium niobate photocatalysts (bandgap: similar to 3.1 eV), prepared by a solid-state (SS) reaction and sol-gel (SG) method and dispersed with a noble metal (similar to 0.5% of Pt, Au, or RuOx) cocatalyst. SG-GaNbO4 comprised smaller size particles (similar to 20-50 nm) and a larger surface area (similar to 160 m(2) g(-1)) compared to SS-GaNbO4 (particle size similar to 30-150 nm, surface area similar to 27 m(2) g(-1)). XRD patterns revealed a preparation-dependent variation in the relative intensity of prominent reflections. In TEM examination, SG samples exhibited small-range grain boundaries and heterogeneous metal/substrate interfacial contacts, while SS-GaNbO4 had long-range ordering. Laser-Raman and thermoluminescence investigations revealed that lattice distortion, defect-induced inter-bandgap charge trapping states, and the local environment around the metal/semiconductor interfaces may also depend on the preparation method. Metal-GaNbO4 nanocomposites showed no activity for the dissociation of pure water under UV (>250 nm) irradiation, despite the favourable conduction and valence band potentials. This was attributed to the sharp Ga and Nb d-levels in the narrow conduction band of GaNbO4, as confirmed by ab initio electronic structure calculation. These photocatalysts, however, showed good activity for semiconductor-mediated photo-dissociation of aqueous methanol to produce H-2; a cocatalyst-dependent activity trend, Pt > RuOx > Au, was observed. Doping of S at similar to 5% of the oxygen sites led to decreased photoactivity, ascribed to the presence of localized S 3p states just above the O 2p valence level. In conclusion, besides band characteristics, certain morphological and microstructural properties play a crucial role in the photoactivity of the metal/oxide nanocomposites.

Genesis of enhanced photoactivity of CdS/Ni-x nanocomposites for visible-light-driven splitting of water - Devi, Suman; Korake, Prakash V.; Achary, Srungarpu N.; Gupta, Narencira M. (International Journal of Hydrogen Energy, 2014)
A series of CdS/Ni-x nanocomposite photocatalysts, containing ca. 0.6-15 wt% Ni, were synthesized using a one-step hydrothermal method and characterized for their crystallographic, morphological, interfacial, and optical properties. Rietveld refinement of powder XRD data revealed the coexistence of wurtzite (hexagonal) and zinc blende (cubic) phases of CdS in ratios dependent on Ni content. Only a fraction of Ni existed as a secondary phase of NiS while the majority occupied the lattice positions of hexagonal CdS. Whereas up to 10-fold enhancement in H-2 evolution compared with pure CdS was observed for samples containing similar to 1.5-4.5 wt% Ni, samples with smaller or larger Ni content displayed poor activity for visible-light-induced splitting of water in presence of sulfide-sulphite ions as sacrificial electron donors. In contrary to recent findings, our study reveals that the enhanced CdS photoactivity is not a result of charge transfer between p-type NiS and n-type CdS, Ni-induced visible-region absorbance, or the coating of CdS particles by non-photoactive NiS. Instead, the preparation-dependent hexagonal/cubic CdS phase boundaries and particle morphology may play a crucial role. Additionally, certain Ni-doping-induced sub-bandgap shallow energy levels contribute to charge carrier separation. Copyright (C) 2014, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: CdS/Ni-x nanocomposites; Dominant hexagonal facets; Enhanced photoactivity; Hydrogen evolution; Phase boundary effects; water splitting

Deciphering the role of temperature in Li+ co-dopant occupancy in BaYF5:Yb3+,Er3+ up-converting nanocrystals and its structure-property relationship - Devi, Suman; Luwang, Meitram Niraj (Journal of Chemical Physics, 2021)
Precision engineering of defects in luminescent nanoscale crystalline materials with lesser controls to design is an area of interest in engineering materials with desired properties. Li+ co-doped BaYF5 nanocrystals were engineered, and temperature as controls for determining the co-dopant occupancies in the host lattice is studied. An observed enhancement in the up-conversion photoluminescence results from the co-dopant occupancy at Ba2+ sites via substitution through the hot injection method, whereas for samples prepared using co-precipitation, photoluminescence quenching was observed, which can be correlated with the Li+ occupancy at the interstitial site near Er3+ and also due to the incorporation of OH-. The crystal lattice deformation as a result of doping and the mechanism for the observed enhancement/quenching of luminescence are studied using x-ray diffraction, x-ray photoelectron spectroscopy, and energy transfer mechanism. Cytotoxicity assay and photoluminescence studies of the synthesized nanocrystals confirm that the material is biocompatible.

Engineering luminescent carbon dot emission through surface state functional group via heteroatom doping and unveiling the effect of solvents - Devi, Suman; Luwang, Meitram Niraj (Langmuir, 2025)
This work comprehends the synthesis of carbon dots from papaya leaves (PCD) using water, ethanolamine (EA), and dimethylformamide (DMF). Ethylenediamine (EDA) was used to introduce nitrogen doping. Water-based PCDs emit blue light, while those in EA and DMF emit red light due to increased oxidation. In EA or DMF with EDA, red emission quenches, and enhanced blue emission is observed, which infers reduced oxidation. This indicates that EDA shifted the emission back to the blue. These findings were confirmed by hypothetical mechanistic studies, Raman spectroscopy, and X-ray photoelectron spectroscopy (XPS). The Raman spectrum revealed defect-activated D and G bands; defects increase in pure solvents compared to water but decreases in mixed solvents such as EA + EDA and DMF + EDA. In XPS, C-O bonds were detected at a higher level in EA and DMF, whereas C-N bonds were observed at a higher level in EDA. TEM images showed that the synthesized PCDs ranged from 1 to 5 nm, with interplanar spacing values consistent with X-ray diffraction (XRD) analysis. PCDs synthesized from a sustainable carbon source exhibit tunable fluorescence from blue to red and vice versa based on solvents used during the engineering of surface state functional group. This makes them promising candidates for fluorescent security inks.

Precursor-dependent heteroatom diversity in luminescent carbon quantum dots: their impact on physicochemical properties and free radical scavenging and antibacterial activities - Konwar, Pollab Mohan; Devi, Suman; Pandey, Satish Kumar; Devi, Khomdram Sandhyarani; Devi, Ayekpam Bimolini; Luwang, Meitram Niraj (Langmuir, 2025)
The fabrication of a multifunctional carbon quantum dot (CQD) from a novel carbon source is still continuing to be demanding and fascinating. The carbon precursor plays a crucial role in developing any particular properties of a CQD to suit a specific application. In this study, green (Rhus chinensis fruits) as well as chemical-based (ascorbic acid and urea) carbon sources were used for the fabrication of CQDs using a simple, cost-effective, and eco-friendly method. The various physicochemical and optical properties of R. chinensis fruit-derived CQD (CQD-RCF) and urea-assisted ascorbic acid-derived CQD (CQD-AAU) were thoroughly investigated by using multiple characterization techniques such as XRD, TEM, HR-TEM, Raman, XPS, FT-IR, UV-vis, PL, and zeta potential. The synthesized CQDs were screened for antioxidant properties by a DPPH assay and antibacterial activity by the agar tip-well method. Both of these synthesized CQDs exhibited a variety of dissimilarities regarding their heteroatom compositions and surface functional groups, which subsequently led to an enhanced DPPH radical scavenging efficacy of CQD-AAU and a declared antibacterial efficacy of CQD-RCF. Therefore, the outcome of this study shows that the physicochemical properties and functionalities of CQDs are influenced by the chemical composition of the precursor material.